Multiplicative conformable fractional Dirac system - Goktas, Sertac; Kemaloglu, Hikmet; Yilmaz, Emrah (Tubitak Scientific & Technological Research Council Turkey, 2022)
In multiplicative fractional calculus, the well-known Dirac system in fractional calculus is redefined. The aim of this study is to analyze some spectral properties such as self-adjointness of the operator, structure of all eigenvalues, orthogonality of distinct eigenfunctions, etc. for this system. Moreover, Green's function in multiplicative case is reconstructed for this system.
Keywords: Conformable Dirac system; Multiplicative conformable fractional derivative; Multiplicative conformable fractional integral; Multiplicative Dirac system; Non-Newtonian calculus